Triple diffusive flow of nanofluid with buoyancy forces and nonlinear thermal radiation over a horizontal plate. Issue 8 (27th July 2018) - Archana, M.; Reddy, M. G.; Gireesha, B. J.; Prasannakumara, B. C.; Shehzad, S. A.
Abstract: The present attempt is made to elaborate the features of triple diffusive convective flow of an incompressible nanoliquid induced by horizontal surface under buoyancy forces. The effect of nonlinear thermal radiation is taken into account. Heat flux model of radiation is formulated through Rosseland's approximation. The radiation phenomenon plays a key role in modern solar energy equipment's. The nondimensional variables are introduced to convert the dimensional mathematical expressions into dimensionless single independent variable. Numerical scheme is developed to obtain the solution of mathematical model. The importance of controlling constraints on flow quantities are characterized through plots. The quantities of engineering importance are computed and elaborated graphically. It is noticed that the presence of salts and nanoparticles enhance the thermal performance of base liquid. The liquid temperature and its relevant thickness of thermal layer improved significantly with an increment in the values of radiative parameter. The larger values of parameters of Brownian motion and thermophoretic correspond to higher temperature profiles.